Orbital intravascular papillary endothelial hyperplasia in a Nigerian child: a case report and review of the literature - Fasina, Oluyemi (BioMed Central, 2012)
INTRODUCTION: Intravascular papillary endothelial hyperplasia is a reactive proliferative lesion of endothelial cells in blood vessels. It typically presents as a painless, reddish purple lesion in the sites affected. The orbit remains an uncommon site of affectation of this relatively common disease. It is noteworthy that this is the first reported case, to the best of our knowledge, of orbital intravascular papillary endothelial hyperplasia in a Nigerian child. CASE PRESENTATION: The case reported here is an orbital intravascular papillary endothelial hyperplasia causing non-axial proptosis and loss of vision in a 14-year-old Nigerian boy. We describe the clinical and histological findings of intravascular papillary endothelial hyperplasia in the orbit of this 14-year-old boy. The key distinguishing features are discussed and relevant literature is reviewed. CONCLUSION: Although unusual in presentation, intravascular papillary endothelial proliferation should be considered in the list of differentials of proptosis due to mass lesion in young Nigerians and, possibly, Africans.